(untitled) (Docentes 2.0 Journal, 2026)
Videos have emerged as a significant tool for disseminating academic and scientific material, particularly in digital environments where students primarily consume information in audiovisual formats. The objective of this study was to analyze which elements or factors of audiovisual communication predict the perception of scientific dissemination among Social Sciences students at the National University of Tumbes during the 2025 period. The research was framed within the positivist paradigm, employing a hypothetico-deductive method and a quantitative approach, under a non-experimental, correlational-explanatory, and cross-sectional design. The study population consisted of 1,124 students, from which a probabilistic sample of 347 participants was selected. Two structured questionnaires featuring a five-point Likert scale were administered; these instruments were organized by dimension and validated through expert judgment, while their reliability was estimated using McDonald’s Omega coefficient. Data were analyzed using descriptive statistics, Kolmogorov-Smirnov normality tests, Spearman’s rho correlation, and ordinal logistic regression to identify predictive factors. The results demonstrated that the probability of ranking within higher levels of perceived scientific dissemination increased when the videos featured a coherent and easily understandable message (P10; OR=1.805; p=0.004), relevant content (P11; OR=1.579; p=0.011), the integration of text or graphics (P14; OR=1.580; p=0.037), and fluid camera shots and angles (P4; OR=1.435; p=0.042). Furthermore, the overall correlation between audiovisual communication and scientific dissemination was positive and statistically significant (Rho = 0.194; p = 0.001), albeit of low magnitude. When analyzed by dimension, morphology, semantics, and aesthetics exhibited significant, though weak, associations, whereas syntax and expression did not reach statistical significance.